Le paysage serait-il une forme surannée ? Mise en représentation de la ville, art urbain et pratiques transitoires - Paquet, Suzanne (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2010)
This essay raises the question of the role remaining to art in today’s vision and practice of landscape. Between the social demands attached to the concept of landscape and the ethical concerns linked to sustainable development, it seems that landscape has become a foreign body within artistic practice. Landscape is now often considered as an object, a piece of land shaped by human use that can even be completely reshaped by landscape architects and other professionals. Paradoxically, this point of view has been, at least in part, inspired by the work of the land artists who worked in the 1960s and 1970s: they conceived a model so strong and operative that it became a formula, and this formula has been appropriated by extra-artistic practitioners. Perhaps landscape must now be evacuated from the field of art. Certain specific instances from the Montréal context support this argument, and certain contemporary artistic interventions suggest a means of resistance to the results of the “landscaping” of cities.